You're Not from Around Here, Are You? - Blum, Louise A. (The University of Wisconsin Press, 2023)
This is a funny, moving story about life in a small town, from the point of view of a pregnant lesbian. Louise A. Blum, author of the critically acclaimed novel Amnesty, now tells the story of her own life and her decision to be out, loud, and pregnant. Mixing humor with memorable prose, Blum recounts how a quiet, conservative town in an impoverished stretch of Appalachia reacts as she and a local woman, Connie, fall in love, move in together, and determine to live their life together openly and truthfully.